IDENTIFICATION, DISTRIBUTION, AND TESTING THE LEVEL OF Sternochetus (Sternochetus sp, COLEOPTERA: CURCULIONIDAE) ATTACK AND THE HOST STATUS USING NO-CHOICE TEST - Syahputra, Ade; Ahad, Mustopha; .,, Abdurakhman; Hidayat, Joni (Universitas Lampung, 2019)
Mango pulp weevil (MPW) and mango seed weevil (MSW) are found in only three species in the world, namely Sternochetus frigidus (MPW), Sternochetus mangiferae (MSW) and Sternochetus olivieri (MSW). These pests are the main pests for mango in several countries including Indonesia. But there is currently no report on the status of the three insects of Sternochetus in Indonesia, so that the information received by the Center for Agriculture and Biosciences International (CABI) as a worldwide plant pest data center is based on Kalshoven (1981). The purpose of this study was to identify species, to test the attack level and to conduct no-choice test on Sternochetus host in mango. This study was conducted at the Applied Research Institute of Agriculture Quarantine from March to October 2017. Kuweni fruit (Mangifera odorata) that was confirmed to be infested by Sternochetus insect was collected from Pesisir selatan District of West Sumatra, North Lampung District, Lubuk Linggau District of South Sumatera and Bekasi District of West Java Provinces respectively. The species identification was performed on the male genital (aedeagus) of the insect, which was obtained from the Kuweni fruit aged 95-115 days. The fruit collection from the three locations have identified S. frigidus species, with overlapping apical sclerite characteristics. In Bekasi District, S. frigidus insect could not infest the Kuweni fruit. Attack level test of S. frigidus in kuweni fruit in all three locations reached 93%. The result of host status test with no choice test showed that S. frigidus was able to infest harum manis and manalagi mango (Mangifera indica) and did not infest sapodilla fruit.